Gender Reflections: a Reconsideration of Pictish Mirror and Comb Symbols - (:unkn) unknown (My University, 2016)
The interpretation of prehistoric iconography is complicated by the tendency to project contemporary male/female gender dichotomies into the past. Pictish monumental stone sculpture in Scotland has been studied over the last 100 years. Traditionally, mirror and comb symbols found on some stones produced in Scotland between AD 400 and AD 900 have been interpreted as being associated exclusively with women and/or the female gender. This thesis re-examines this assumption in light of more recent work to offer a new interpretation of Pictish mirror and comb symbols and to suggest a larger context for their possible meaning. Utilizing the Canmore database, 272 Pictish monumental sculpture were contextually compared with each other in light of archaeological and historical data. Mirrors and combs appear together or the mirror and comb individually appear on 66 (24.3%) stones. Of these, only eight (2.9%) sculptures are depicted with human figures. The results of this analysis suggest that the mirror and comb symbols were not associated exclusively with women but rather represent actual objects imbued with special meaning as well as symbols of particular lineages and their association with specific sociopolitical roles in Pictish society.
Keywords: Gender; Iconography; Inalienable Objects; Picts; Power; Scotland